DAMPAK TRANSFORMASI PERAN WANITA DALAM PEMBANGUNAN TERHADAP DINAMIKA SISTEM KEPENDUDUKAN INDONESIA - Ahmad Basuki (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
The change of social pattern from traditional agrarian into modern industry has impact in woman transformation role. The previously woman role in the ‘back side’ or ‘under the man shadow’ begins to start into questions. Egalitarianism motto becomes familiar together with the extension of woman role. Anyhow, such change should be responded with a clear and specific policy. Accordingly, law as a tool of social engineering should be able to accommodate them, as well as gives the guarantee for the extension of woman role that has been once pushed in a corner by feudalism tradition.